AQUAPONICS SYSTEM FOR SMALL VEGETABLE PRODUCERS - Bragantin da Silva, Fernanda Camila (Revista Interface Tecnológica, 2023)
Aquaponics is a cultivation system that has the junction of two distinct crops, aquaculture which is the raising of fish and hydroponics which is the cultivation of plants and vegetables without the use of soil. Aquaponics is a sustainable cultivation system where it saves water and eliminates the use of chemicals such as pesticides and fertilizers, using the residues eliminated by fish as a form of nutrients for plants, a crop for small producers where they take their monthly income from both fish farming and vegetable cultivation. One of the main advantages of this system is that it can be installed in small areas having the maximum use, using few resources, using even water tanks, buckets and pipes, obtaining a high productivity without having significant losses, the disadvantages is the lack of technology, knowledge in the area, constant use of electricity and constant monitoring of water. Within this context, the present work aims to show how an aquaponic system works through aquaculture and hydroponics, showing its functionality and which species of crops and fish farming most used, the environmental control that in aquaponics comes as one of the alternatives using biodigester in the waste that are at the bottom of the decanter generating biogas instead of disposing of these residues in the environment, being able to use this biogas in the form of electrical energy for the aquaponic system itself.